Antigen-Specific Immune Modulation Targets mTORC1 Function to Drive Chemokine Receptor-Mediated T Cell Tolerance - Chen, Weirong (J Immunol, 2016)
To contain autoimmunity, pathogenic T cells must be eliminated or diverted from reaching the target organ. Recently, we defined a novel form of T cell tolerance whereby treatment with antigen (Ag) downregulates expression of the chemokine receptor, CXCR3 and prevents diabetogenic Th1 cells from reaching the pancreas leading to suppression of Type 1 diabetes (T1D). This report defines the signaling events underlying Ag-induced chemokine receptor-mediated tolerance. Specifically, we show that the mammalian target of rapamycin complex 1 (mTORC1) is a major target for induction of CXCR3 down-regulation and crippling of Th1 cells. Indeed, Ag administration induces up-regulation of programmed death-ligand 1 (PD-L1) on dendritic cells (DCs) in a T cell-dependent manner. In return, PD-L1 interacts with the constitutively expressed PD-1 on the target T cells and stimulates docking of SHP-2 phosphatase to the cytoplasmic tail of programmed death-1 (PD-1). Active SHP-2 impairs the signaling function of the phosphatidylinositol-3-kinase/protein kinase B (PI3K/AKT) pathway leading to functional defect of mTORC1, down regulation of CXCR3 expression and suppression of T1D. Thus, mTORC1 component of the metabolic pathway serves as a target for chemokine receptor-mediated T cell tolerance and suppression of T1D.